Virtuosos of Mimesis and Mimicry: a Case Study of Movements Propagating Conspiracy Theories in Ireland and Poland - Drążkiewicz, Elżbieta (PARTECIPAZIONE E CONFLITTO, 2023)
In recent years, conspiracy theories have been increasingly defined as a new social enemy, a threat to democracy. But scholars of conspiracy theories also point out that we have very little research that examines a direct link between conspiracy theories and political practice. We still know very little about the ways in which conspiratorial beliefs influence different forms of civic engagement and democratic participation. By examining Irish and Polish movements that endorse vaccination-related conspiracy theories, this article explores what relation they have to civil society. I argue that, in order to shed the negative label of conspiracy theories, such movements engage in the practices of mimesis and mimicry. According to Markus Hoehne, mimesis is a form of positive appraisal, an art of imitating well-established models of social and political organization. Mimicry, on the other hand, involves the deceptive imitation of such models in order to attain one's own political agenda. What, then, are the Covid-19 era protests: masters of mimicry or masters of mimesis?